When water security programmes seek to empower women-a case study from western Nepal - Clement, Floriane; Karki, Emma (2017)
Women’s empowerment has been a key tenet of international water security programmes. Discourses on water envision that enhanced access to water resources can transform disempowered women into successful rural entrepreneurs. However, because such programmes often rely on simplistic representations of water, gender relations, and empowerment, they risk perpetuating and exacerbating gender inequalities. Our study unpacks the storylines that drive water security interventions in the rural Global South, based on the case study of a donor-funded project in Nepal. The latter explicitly aimed at empowering women by improving their access to water for domestic and productive uses and by transforming women into rural entrepreneurs and grassroots leaders. We largely used qualitative methodologies, based on focus group discussions and semi-structured interviews with households and key informants. Fieldwork was conducted in two villages targeted by the programme located in two districts of Far-Western Nepal. Our findings show that the gender myths and models that drive water security programmes, e.g. women as individual decision-makers and entrepreneurs, fail to adequately consider intra-household relationships and negotiations and the values that give meaning to women’s agency. Such programmes tend to perpetuate predominant gendered norms, practices and unequal power relationships within households and communities. We recommend that water security programmes rely on more nuanced and context-specific understandings of women’s empowerment that go beyond enhanced access to resources and agency to include knowledge, critical consciousness and values. It is also important that such initiatives involve men and women – rather than exclusively targeting women – and initiate critical reflections on gender roles and masculinities.